Analisis Studi Kebijakan Terhadap Standar Pembiayaan (Telaah Permendikbud Nomor 26 Tahun 2017 Tentang Petunjuk Teknis BOS) - Lestari, Dirga Ayu; Mutaqin, Mumu Zainal; Muhdiyati, Iyon (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2024)
Regulation of the Minister of Education and Culture (Permendikbud) Number 26 of 2017 concerning Instructions and Techniques for School Operational Assistance is a form of the state's commitment to fulfilling the demands of the opening of the 1945 Constitution. Through this Minister of Education and Culture Regulation, it is hoped that national education will be able to guarantee equal distribution of educational opportunities, improve the quality and relevance and efficiency of education management especially on financing standards to face challenges in the era of globalization. Several important points in this Permendikbud are the ease of learning with the existence of free compulsory education (fair) for 12 years, namely SD/MI, SMP/MTs and SMA/MA. Thus, the commitment made by the government must of course be supported by other stakeholders so that this program can be realized and is on target. So that there will be no issues related to the free 12th compulsory education program which is none other than the existence of BOS/BOM funds.